Instagram Fatwa: Analisis terhadap Pesan Fatwa dalam Akun Instagram @Dakwahquransunnah - Patahillah, Hilman Fauzi (Fakultas Dakwah dan Ilmu Komunikasi, Universitas PTIQ Jakarta, 2020)
In the new media era, information technology has become a multi-functional thing among its users. Especially the Instagram media which has become a new arena for Islamic unity to broadcast its teachings. Instagram has become a forum for Islamic unity in disseminating its fatwa. The purpose of this research is to find out how fatwas are discouraged on Instagram social media. The results of his research are that in the era of new media, it is precisely still reflective of the teachings of purification of religion, because the influence of new media talks very little about social and political matters, and among the followers there is a shift in authority, exactly not up to date on new issues, and always raises old topics that are impressed ancient.